Supply–demand equilibria and multivariate optimization of social welfare in double-ended queueing systems. (August 2022) - Nguyen, Hung Q.; Phung-Duc, Tuan
Abstract: This paper considers a double-ended queueing system in which both the supply and demand sides adopt strategic behaviors in observable and unobservable cases. Systems with only one type of strategic agents are common in literature. Agents in these systems follow the crowd and form a common strategy adopted by all at the evolutionary endpoint, which is usually referred to as the "equilibrium strategy". When both sides are strategic, however, the strategy adopted by any individual on one side depends not only on what the individuals of their own side are doing but also on the other side, which forms a Nash equilibrium between the two sides. To solve for such an equilibrium, we extend the existing game theoretical framework on queueing problems under the scope of multi-population games. In contrast, in the scenario of sellers and buyers being socially concerned, a joint social welfare function needs a multivariate maximization on the two decision variables. We solve multivariate optimization problems in both observable and unobservable cases to find socially optimal strategies for both sides. Highlights: A double-ended queueing system with strategic agents on both sides. Nash equilibria derived from a multi-population game theoretical framework. Multivariate optimization of the system. Policies that simultaneously regulate behaviors of both sides.